The role of global health partnerships in vaccine equity: A scoping review. - Charnele Nunes; Martin McKee; Natasha Howard (Public Library of Science (PLoS), 2024)
The emergence of global health partnerships (GHPs) towards the end of the twentieth century reflected concerns about slow progress in access to essential medicines, including vaccines. These partnerships bring together governments, private philanthropic foundations, NGOs, and international agencies. Those in the vaccine field seek to incentivise the development and manufacture of new vaccines, raise funds to pay for them and develop and support systems to deliver them to those in need. These activities became more critical during the COVID-19 pandemic, with the COVAX Facility Initiative promoting global vaccine equity. This review identifies lessons from previous experiences with GHPs. Findings contribute to understanding the emergence of GHPs, the mechanisms they leverage to support global access to vaccines, and the inherent challenges associated with their implementation. Using Arksey and O'Malley's method, we conducted a scoping review to identify and synthesise relevant articles. We analysed data thematically to identify barriers and opportunities for success. We included 68 eligible articles of 3,215 screened. Most (65 [95%]) were discussion or review articles describing partnerships or programmes they supported, and three (5%) were commentaries. Emerging themes included policy responses (e.g., immunisation mandates), different forms of partnerships arising in vaccine innovation (e.g., product development partnerships, public-private partnerships for access), and influence on global governance decision-making processes (e.g., the rising influence of foundations, diminishing authority of WHO, lack of accountability and transparency, creation of disease silos). If global health partnerships are to maximise their contributions, they should: (1) increase transparency, especially regarding their impacts; (2) address the need for health systems strengthening; and (3) address disincentives for cooperative vaccine research and development partnerships and encourage expansion of manufacturing capacity in low and middle-income countries.